Chemistry and liquid chromatography methods for the analyses of primary oxidation products of triacylglycerols. (May 2015) - Zeb, A.
Abstract Triacylglycerols (TAGs) are one of the major components of the cells in higher biological systems, which can act as an energy reservoir in the living cells. The unsaturated fatty acid moiety is the key site of oxidation and formation of oxidation compounds. The TAG free radical generates several primary oxidation compounds. These include hydroperoxides, hydroxides, epidioxides, hydroperoxy epidioxides, hydroxyl epidioxides, and epoxides. The presence of these oxidized TAGs in the cell increases the chances of several detrimental processes. For this purpose, several liquid chromatography (LC) methods were reported in their analyses. This review is therefore focused on the chemistry, oxidation, extraction, and the LC methods reported in the analyses of oxidized TAGs. The studies on thin-layer chromatography were mostly focused on the total oxidized TAGs separation and employ hexane as major solvent. High-performance LC (HPLC) methods were discussed in details along with their merits and demerits. It was found that most of the HPLC methods employed isocratic elution with methanol and acetonitrile as major solvents with an ultraviolet detector. The coupling of HPLC with mass spectrometry (MS) highly increases the efficiency of analysis as well as enables reliable structural elucidation. The use of MS was found to be helpful in studying the oxidation chemistry of TAGs and needs to be extended to the complex biological systems.